2015
DOI: 10.1136/openhrt-2015-000302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of catheter ablation on quality of life in patients with atrial fibrillation and its correlation with arrhythmia outcome

Abstract: ObjectiveTo assess the effect of catheter ablation on atrial fibrillation (AF) symptoms and quality of life (QoL).MethodsPatients with AF scheduled for ablation were recruited. Pulmonary vein isolation (PVI) was performed and complex fractionated atrial electrogram (CFAE)±linear ablation undertaken in patients in AF despite PVI. QoL and AF symptoms were assessed using SF-36 V2 and Atrial Fibrillation Effect on Quality-of-Life (AFEQT) questionnaires before and 3 months after ablation. Change in QoL scores after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…Generic instruments measure general health and functioning and are influenced by patient demographics and comorbidity, while AF‐specific questionnaires were developed specifically to measure AF‐related PROs. Our results suggest that the AF6 is more sensitive than SF‐36 in capturing more components of AF, which is in line with previous studies using other AF‐specific PRO instruments . The potential for comorbidities to impact PRO scores further points to the need for AF‐specific instruments when studying AF interventions.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Generic instruments measure general health and functioning and are influenced by patient demographics and comorbidity, while AF‐specific questionnaires were developed specifically to measure AF‐related PROs. Our results suggest that the AF6 is more sensitive than SF‐36 in capturing more components of AF, which is in line with previous studies using other AF‐specific PRO instruments . The potential for comorbidities to impact PRO scores further points to the need for AF‐specific instruments when studying AF interventions.…”
Section: Discussionsupporting
confidence: 89%
“…Wokhlu et al used the not yet validated Mayo AF‐Specific Symptom Inventory and showed significant improvement in 10 of 12 symptoms 2 years after ablation . Raine et al used a validated AF‐specific instrument, the Atrial Fibrillation Effect on Quality‐of‐Life, before and 3 months after AF ablation and found a significant improvement only in patients without AF recurrence …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the QoL score returned to the pre-procedural level after only several weeks post ablation, staying at the initial level during a long-term follow-up [ 86 ]. The QoL improvement was strikingly higher in patients who were AF-free than in those with recurrent arrhythmia after the procedure [ 86 88 ]. However, even in patients with AF recurrence, a significant QoL improvement was observed following ablation compared to pre-ablation values, possibly because of the higher proportion of asymptomatic arrhythmia episodes, reduction in AF burden, LA denervation, increased AAD effectiveness or placebo effect post procedure [ 88 ].…”
Section: Catheter Ablation Proceduresmentioning
confidence: 99%